PROFIL PRESEPAN OBAT PADA PASIEN PEMBESARAN PROSTAT JINAK ATAU BPH (BENIGN PROSTATIC HYPERPLASIA) TAMSULOSIN DAN DUTASTERIDE DI INSTALASI RAWAT JALAN RUMAH SAKIT “X” CIPUTAT PERIODE OKTOBER-DESEMBER 2024 - Dewantoro, Agung; Dewi, Bheta Sari; Rahajeng, Suny Koswara (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2025)
Benign prostatic hyperplasia (BPH) is a term used in histopathology to describe the presence of enlarged stromal and epithelial cells in the prostate gland. In essence, BPH mostly affects elderly men whose testes are still capable of making testosterone. According to earlier research, using dutasteride and tamsulosin together may have greater therapeutic results for BPH and significantly lower the chance that symptoms may worsen. Purpose: The objective of this study was to identify salient features of Tamsulosin and Dutasteride prescriptions for benign prostatic enlargement (BPH) at Ciputat